2001
DOI: 10.1038/35102054
|View full text |Cite
|
Sign up to set email alerts
|

Rapid responses of British butterflies to opposing forces of climate and habitat change

Abstract: Habitat degradation and climate change are thought to be altering the distributions and abundances of animals and plants throughout the world, but their combined impacts have not been assessed for any species assemblage. Here we evaluated changes in the distribution sizes and abundances of 46 species of butterflies that approach their northern climatic range margins in Britain-where changes in climate and habitat are opposing forces. These insects might be expected to have responded positively to climate warmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
1,098
3
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,156 publications
(1,145 citation statements)
references
References 20 publications
34
1,098
3
10
Order By: Relevance
“…We conclude that these results suggest that patches of habitat in a fragmented landscape are more readily colonized in periods with weather conditions favourable for dispersal. Therefore, we argue that climate change not only aggravates the impacts of habitat fragmentation on populations (Opdam and Wascher Warren et al 2001), but also may diminish these impacts by enhancing dispersal and colonization. This is indeed shown in the successful northwards range expansion of mobile generalist species (Warren et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We conclude that these results suggest that patches of habitat in a fragmented landscape are more readily colonized in periods with weather conditions favourable for dispersal. Therefore, we argue that climate change not only aggravates the impacts of habitat fragmentation on populations (Opdam and Wascher Warren et al 2001), but also may diminish these impacts by enhancing dispersal and colonization. This is indeed shown in the successful northwards range expansion of mobile generalist species (Warren et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we argue that climate change not only aggravates the impacts of habitat fragmentation on populations (Opdam and Wascher Warren et al 2001), but also may diminish these impacts by enhancing dispersal and colonization. This is indeed shown in the successful northwards range expansion of mobile generalist species (Warren et al 2001). Further evidence supporting this view was found by Møller et al (2006), who found increased dispersal tendencies in a coastal seabird, the Arctic tern, in relation with long-term climate change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the restored areas in our study were typically located near forest fragments, our study region is dominated by human-managed habitats such as pastures and Eucalyptus plantations. Forest generalists may be poor competitors, but possess much better dispersal abilities compared to forest-restricted species and are also less sensitive to habitat change (Krauss et al, 2003;Larsen et al, 2008;Warren et al, 2001). Therefore, they can take advantage and dominate newly available environments that have some degree of canopy cover.…”
Section: Species Composition and Categories Of Habitat Specificitymentioning
confidence: 99%
“…There is evidence of shifts in distribution, both latitudinal and elevational, for invertebrates and vertebrates [20][21][22][23][24] as well as changes in phenology [25]. Finally, local extinctions in lizards have been attributed to climate change [8].…”
Section: Introductionmentioning
confidence: 99%